Technology and workflows for multiple channel content distribution : infrastructure implementation strategies for converged production - Cianci, Philip J. (Focal Press media technology professional., 2009)
This book addresses the emergence of multi-channel broadcasting. Televisions, PCs, handheld and mobile reception devices now all receive content hat was once solely distributed by broadcast TV. No book currently on the market addresses the production infrastructure necessary to efficiently produce content for multi-channel delivery to a variety of reception platforms/devices. Readers will acquire an overview of not just the technology, but processes that impact the creative process and new cross-platform advertising sale/buy model. *Integrated, parallel production workflows design techniques for multi-channel distribution are discussed *Facilitates an understanding of the inherent challenges in producing and distributing content for multiple consumption devices *Connects consumer technology with production infrastructure *Ties together all other technical books that deal with each topic individually: i. e DTV, IPTV, Internet, Mobile TV.